Synthesis of Co3+ Doped TiO2 by Co-precipitation Route and Its Gas Sensing Properties - Lontio Fomekong, Roussin; Saruhan, Bilge (Frontiers in Materials, 2019)
Abstract Undoped and Co-doped TiO2 nanoparticles were synthesized by a facile co-precipitation method and calcined at 700°C. The phase identification carried out by XRD measurements and Raman spectroscopy analysis of calcined powders reveals the formation of mainly anatase phase for undoped TiO2, and 0.5 mol % Co-doped TiO2 whereas rutile phase for 1 mol % Co-doped TiO2. The sensors prepared with these powders deposited on interdigital (IDE) sensor platforms were tested toward NO2 and H2 sensing properties at 600 °C. As the undoped and 0.5 % Co-doped TiO2 reveal n-type behavior, 1 % Co-doped TiO2 shows p-type semi-conductive behavior. 1 % Co-doped TiO2 exhibits good sensing performance toward NO2 while the undoped TiO2 powder yields the best sensor performance toward H2 at 600°C. This indicates that the crystal structure of TiO2 sensing material must be adjusted depending on the nature of target gas. The results indicate that the main factor influencing high temperature gas sensor performance of nanoparticulate TiO2 is either the alteration of its electronic structure or the type of polymorphs.